Impact of archived M184V/I mutation on the effectiveness of switch to co-formulated elvitegravir, cobicistat, emtricitabine and tenofovir alafenamide among virally suppressed people living with HIV. (31st July 2020) - Chen, Guan-Jhou; Lee, Yu-Lin; Lee, Chen-Hsiang; Sun, Hsin-Yun; Cheng, Chien-Yu; Tsai, Hung-Chin; Huang, Sung-Hsi; Lee, Yi-Chieh; Hsieh, Min-Han; Chang, Sui-Yuan; Chuang, Yu-Chung; Su, Li-Shin; et al.
Abstract: Objectives: Real-world experience regarding the effectiveness of co-formulated elvitegravir, cobicistat, emtricitabine and tenofovir alafenamide (EVG/C/FTC/TAF) as a switch regimen is sparse among people living with HIV (PLWH) harbouring the M184V/I mutation with or without thymidine analogue-associated mutations (TAMs). Methods: In this retrospective multicentre study, PLWH who were switched to EVG/C/FTC/TAF after having achieved viral suppression (plasma HIV RNA <200 copies/mL) for 6 months or longer were included. Patients with archived M184V/I mutation (case patients) were matched to controls without M184V/I mutation at a 1:4 ratio. Patients with a history of virological failure or resistance to elvitegravir were excluded. The primary endpoint was virological non-success (plasma HIV RNA ≥50 copies/mL) at Week 48 of switch using a modified FDA snapshot analysis. Results: Overall, 100 case patients with the M184V/I mutation were identified, including 6 (6.0%) with K65R and 13 (13.0%) with at least one TAM, and were matched to 400 controls in terms of gender, age (mean = 40.3 versus 39.7 years) and cumulative exposure duration to tenofovir disoproxil fumarate (median = 146 versus 143 weeks). At Week 48, the rate of virological non-success for the case patients and controls was 5.0% (5/100) and 3.3% (13/400), respectively (difference = 1.7%; 95% CI = −2.9%–6.3%), while the rate of virological success was 88.0% and 89.5% for the case patients and controls, respectively. The presence of the K65R mutation or TAMs was not associated with virological non-response. Conclusions: Among virally suppressed PLWH, EVG/C/FTC/TAF is effective in maintaining viral suppression at Week 48 despite archived M184V/I mutation with or without TAMs.